Characterization of Soils in East And West Zones of Kano River Irrigation Project, Nigeria - Mohammed, D.; Maina, M. M.; Audu, I.; Tudun Wada, I .Y.; Nasiru, N. K.; Raj, Abhishek (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
The relationship between clay composition and on organic matter content, Saturated Hydraulic Conductivity, bulk density and location of soils in a different part of the Kano River Irrigation Project (KRIP) was studied by taking soil samples from forty (40) sectors. Sampling was done from the depth of 0-45 cm with soil auger, digger, a wooden plank and core samplers. Particles size analysis has shown that the percentage of clay varies from the range of 22.12% to 5.4% as observed in Raje and Butalawa respectively. The texture in most of the sectors was dominated by sandy loam. The organic matter (OM) content is typical of agricultural topsoil as all the sectors have organic matter within the range of 1–6%. Spearman correlation coefficient of 0.452 indicates that the relationship between % clay and Bulk density was more of a non-linear relationship than linear. The Pearson correlation coefficient of 0.876 between % clay content of the soil in all the sectors and saturated hydraulic conductivity represents a strong negative relationship between the variables, as % clay content increases, the strength of Sat. hydraulic conductivity tends to decrease. The % clay has no relationship with location of sectors based on the correlation analysis. The Pearson and Spearman coefficients between % Clay content and % OM were 0.407 and 0.473 respectively and this represent a positive relationship between the variables. It was recommended that organic matter content, saturated hydraulic conductivity and bulk density can be used as one of the determinant variables in the development of a model aimed at predicting the % clay of soils in KRIP. Application of organic manure and fertilizer to improve soil productivity and buffering capacity was also recommended due to low organic matter content.